2000
DOI: 10.1097/00007890-200007270-00020
|View full text |Cite
|
Sign up to set email alerts
|

Graft-Versus-Leukemia Effect in Minor Antigen Mismatched Chimeras Given Delayed Donor Leucocyte Infusion: Immunoregulatory Aspects and Role of Donor T and Asgm1-Positive Cells1

Abstract: In minor antigen mismatched BM chimeras, anti-host reactivity after DLI is characterized by (1) an absence of clinical GVHD, (2) clonal deletion of host-reactive CD8 cells, (3) an absence of anti-host CTL induction, and ( 4) a temporary persistence of host-reactive CD4 T cells and of MLR reactivity. In addition, either donor ASGM1+ cells or an interaction between these cells and T cells contribute to the GVL effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 29 publications
5
20
0
Order By: Relevance
“…They were weighed and scored for GVHD weekly. Signs of GVHD typically observed in this model are weight loss, ruffled fur, hunched posture, diarrhea and lethargy, 4,30,31 in accordance with other mouse models of GVHD. 32 On the basis of the published clinical GVHD scores, each parameter was scored as follows: 0 ¼ normal, 1 ¼ mild, 2 ¼ moderate and 3 ¼ severe.…”
Section: Assessment Of Gvhdsupporting
confidence: 86%
“…They were weighed and scored for GVHD weekly. Signs of GVHD typically observed in this model are weight loss, ruffled fur, hunched posture, diarrhea and lethargy, 4,30,31 in accordance with other mouse models of GVHD. 32 On the basis of the published clinical GVHD scores, each parameter was scored as follows: 0 ¼ normal, 1 ¼ mild, 2 ¼ moderate and 3 ¼ severe.…”
Section: Assessment Of Gvhdsupporting
confidence: 86%
“…In a selected experiment, we included a group of mice treated with donor lymphocyte infusion and leukemia challenge, and confirm previous studies, 16,18 the DLI-challenged group showed 66% long-term survival after leukemia challenge ( Figure 2). …”
Section: Recipient Lymphocyte Infusion Induces a Late-onset And Partisupporting
confidence: 58%
“…This chimerism evolution is in contrast with the rapid conversion from mixed to full donor chimerism following donor lymphocyte infusion in the same experimental model 18 and with strong lymphohematopoietic alloreactivity generally seen in patients after donor lymphocyte infusion therapy. [4][5][6][7][8] We postulate that following lethal irradiation, infused healthy donor bone marrow cells have a competitive advantage over residual host-type bone marrow cells and that adoptively transferred donor lymphocytes reinforce this effect, leading to a rapid conversion from mixed to full donor chimerism.…”
Section: Discussionmentioning
confidence: 77%
“…15,16 Similarly, in animal models of allo BMT, donor lymphocytes (DLs) can be safely infused, once a sufficient time interval after transplantation has elapsed. [17][18][19][20][21][22][23] Moreover, in murine bone marrow (BM) chimeras, DLI did induce distinct GVL effects. 17,21,22 These and other clinical and experimental data indicate that, whereas GVH and GVL responses may share effector cells and target antigens, the GVL effect may be dissociated from GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, GVHD was avoided when DLI was delayed for 3 weeks after BMT while a distinct GVL response was allowed to develop. 21 In the present study, DLI was performed at different time points after BMT, as from the moment that DLI was previously shown to be safe. 21 The capacity of DLs to induce a GVL response was studied and was related to the degree of pre-existing chimerism and to the extent to which DLs were able to elicit alloreactivity in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%